Clinical surgery (Blackwell Science, 1996)
The book combines symptoms and signs with a comprehensive overview of surgical practice; stresses that common things are common by prioritizing the 'core' information; is deal for revision with 52 'At a Glance' boxes summarizing the important features of the common surgical diseases; emphasizes the importance of clinical skills in a section on history taking, examination and investigations; highlights the surgical emergencies in a section on the management of acute surgical illness and trauma; gives a comprehensive overview of general and specialist surgery in which each system has a section on clinical evaluation of the patient, pathology, clinical features and management of the diseases; integrates basic science wiht clinical surgery by covering the pathophysiology of diseases; includes chapters on orthopaedics and musculoskeletal trauma